Educational Management In Improving The Quality Of Learning - Okpatrioka Okpatrioka; Sopian Sopian (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This article aims to examine the application of learning management to improve the quality of education. The focus of this research is the concept of educational management in improving the quality of learning, which is broken down into five sub-focuses: (1) the objectives of R&D research in education, (1) the application of educational management in the school environment, (2) effective educational management to improve teacher performance and improve the quality of learning, (3) the role of educational management in improving the quality of teaching, (4) educational management strategies to improve teacher performance, and (5) supporting factors in improving teacher performance. This research used a qualitative method with a literature review. The results illustrate the need for learning management to improve abilities and skills to support the implementation of a quality education process.